PS 06-07 GENDER DIFFERENCES ASSOCIATED BETWEEN SERUM URIC ACID AND MORNING HOME BLOOD PRESSURE MONITORING (MHBPM) PREVALENCE IN THE JAVANESE POPULATION IN INDONESIA. (September 2016) - Sja'bani, Mochammad; Irijanto, Fredie; Widiatmoko, Agus; Alatas, Haidar; Kuswadi, Iri; Zulaela, Dharmaizar; Bawazier, Lucky Azizah; Kholiq, Abdul; Arisma, Elok; Tomino, Yasuiko
N/A: Objective: Measurements in morning home/neighboring blood pressure monitoring can be more valid to predict hypertension occurrence or result. Hypertension prevalence is reanalyzed from this research data and randomized serum uric acid on hypertension occurrence on Javanese Mlati people. Serum uric acid is reported to be lower on women than men. It has not been reported between genders, serum uric acid on blood pressure in the same population. Design and method: A complete reanalysis data was performed in 2007, from 12, 073 of 50, 000 people were more than 17 years old randomly 3 villages with 44 sub villages. Then, the uric acid data was taken randomly from 387 people (165 men and 222 women). A comparison on serum uric acid based on gender was done in hypertension group. Results: Regular hypertension prevalence was included (systolic > 140 mmHg, diastolic > 90 mmHg) 19.6%, in MHBPM (systolic > 135 mmHg, diastolic > 85 mmHg) 23.3%. Regular pre hypertension prevalence (systolic = 120-139 mmHg, diastolic = 80-89 mmHg) 53.7%, and MHBPM (systolic > 120-134 mmHg, diastolic > 80-84 mmHg) 50%. Normal prevalence in regular and MHBPM, the percentage is the same, 26.7%. Serum uric acid on men and women groups were significantly associated with blood pressure height either in regular (P = 0.000) or MHBPM (P = 0.0001) group. Analysis of the uric acid levels on women was significantly different with MHBPM (P = 0.011), regular (P = 0.004), while men with MHBPM calculation (P = 0.122) and regular (P = 0.117). Conclusions: Prevalence hypertension in MHBPM was higher, but pre hypertension was lower than regular classification. The levels of uric acid associated with hypertension level was only in women but not in men in this population.